1984
DOI: 10.1016/0014-5793(84)80844-3
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of oxygen consumption and microcirculation by α‐sympathetic nerves in isolated perfused rat liver

Abstract: In isolated rat liver perfused at constant flow with erythrocyte-free Krebs-Henseleit bicarbonate buffer containing 5 mM glucose and 2 mM lactate, perivascular stimulation of the hepatic nerves caused a rapid decrease of oxygen uptake, a decrease of the periportal and, after a transient rise, of the perivenous tissue PO, of surface acini, an increase of portal pressure, and an enhancement of glucose output. Furthermore, nerve stimulation changed the intrahepatic distribution of the perfusate drastically. Infus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 75 publications
(21 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…Hemodynamic changes after perivascular nerve stimulation, which reduced the perfused parenchymal mass [5], appear to be responsible for the nerve action on urea production, and primarily also on glutamine release and ammonia uptake. This conclusion is based on the following observations and considerations.…”
Section: Mode Of Nerve Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemodynamic changes after perivascular nerve stimulation, which reduced the perfused parenchymal mass [5], appear to be responsible for the nerve action on urea production, and primarily also on glutamine release and ammonia uptake. This conclusion is based on the following observations and considerations.…”
Section: Mode Of Nerve Actionmentioning
confidence: 99%
“…It was shown previously that in the isolated perfused rat liver electrical stimulation of the nerve bundles around the hepatic artery and the portal vein resulted in an increase of glucose output, a switch from lactate uptake to output and a decrease of portal flow [4] combined with a change of the intrahepatic microcirculation [5, 61, a reduction of oxygen uptake [5,7] and an overflow of noradrenaline into the hepatic vein [8]. All nerve actions were predominantly aadrenergic.…”
mentioning
confidence: 99%
“…In the isolated rat liver perfused in situ it has been shown that electrical stimulation of the nerve bundles around the portal vein and the hepatic artery caused hemodynamic and a variety of metabolic changes: perfusion flow was reduced [5,6]. The flow reduction was accompanied by a redistribution of the hepatic microcirculation [7,8]. Glucose and lactate • output increased [5,6], and ketone body formation [9], urea and glutamine production as well as ammonia uptake [10] and oxygen consumption decreased [7,8,11]; furthermore para-nitrophenol conjugation decreased [12] and glutathione efflux increased [13].…”
Section: Introductionmentioning
confidence: 99%
“…The flow reduction was accompanied by a redistribution of the hepatic microcirculation [7,8]. Glucose and lactate • output increased [5,6], and ketone body formation [9], urea and glutamine production as well as ammonia uptake [10] and oxygen consumption decreased [7,8,11]; furthermore para-nitrophenol conjugation decreased [12] and glutathione efflux increased [13]. Stimulation of the nerve bundles also caused an overflow of noradrenaline into the Correspondence address: G.P.…”
Section: Introductionmentioning
confidence: 99%
“…Nerve stimulation caused a decrease of flow [7, 81 combined with a redistribution of the intrahepatic microcirculation [ 11,151 and was accompanied by an overflow of noradrenaline into the hepatic vein [8, 161 and a transient release of calcium and uptake of potassium [14]. All nerve actions were mediated predominantly via sympathetic receptors and required extracellular calcium.…”
mentioning
confidence: 99%